Gendered evaluation of impacts of landscape degradation and restoration on ecosystem services: perspectives from paired husbands and wives in Ethiopia - Mponela, Powell; Aynekulu, Ermias; Ebrahim, Mohammed; Abate, Tsion; Abera, Wuletawu; Elias, Marlène; Tamene, Lulseged D. (Authorea, Inc., 2022)
Globally, land degradation disproportionally affects women more than men and, to close the gender gap, several landscape restoration projects promote gender inclusiveness. However, empirical evidence based on gender-disaggregated data is a major research gap. Using a gender-inclusive restoration case of Amhara and SNNP (Southern Nations, Nationalities and Peoples) regions in Ethiopia in the last 6-10 years, we collected data from 59 wife-husband paired households and six gender-disaggregated focus groups. The study revealed large gender differences in perceptions of landscape scenic beauty and habitat quality in terms of wildlife, pollinators, beneficial plants, weeds, and pests and diseases as indicators of ecological health. Despite that, the paired husbands and wives live together and share resources, their perceptions and valuation of degradation and restoration were divergent. Men largely attributed degradation to external and natural forces while women considered the lack of appropriate restoration strategies as a precursor for accelerated land degradation. Women noted that in areas that receive heavy rainfall and have sleep slopes, cultivation without management measures exacerbates degradation. Gendered experiences on impacts of degradation were captured: women indicated to be greatly impacted in terms of water scarcity for livestock whilst men were impacted on the water for irrigation. On restoration impacts, women display increased concern and knowledge of regulatory services while men are knowledgeable of provision services. Women attribute a moderate impact of land degradation on habitat quality than men and attribute restoration to the enhancement of biodiversity and pollinators. These results are key in understanding the divergence between men’s and women’s valuation of impacts of degradation and restoration that underpins their involvement in ecosystem restoration and can be a basis for gender equity discourse and policy.